2018
DOI: 10.1016/j.adolescence.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of observed autonomy support, reciprocity, and need satisfaction in adolescent disclosure about friends

Abstract: Although research increasingly addresses the role of parenting in fostering adolescent disclosure, most research relied on self-report measures of parenting and did not address the role of autonomy support. In the present observational study (conducted in Belgium), with 62 motheradolescent dyads (mean age mothers = 44 years; mean age adolescents = 14 years; 77% of adolescents female), we rated mothers' provision of autonomy support during a 10-minute conversation about friendships. We found that observed mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 89 publications
4
34
0
Order By: Relevance
“…Indeed, when adolescents perceive parents' initiation of conversations as a sign of caring and interest, they seem to be more willing to share information and, by doing so, they seem to try to maintain a close relationship with them. Moreover, in line with previous studies (e.g., Mageau et al, 2017;Wuyts et al, 2018), perceived maternal and paternal autonomy support were positively related to adolescents' disclosure, and negatively associated with secrecy and lies. In other words, when parents are perceived to provide an autonomysupportive parenting context, for example by being sensitive for their children's feelings and by offering choices whenever possible, their adolescents are more likely to disclose information.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, when adolescents perceive parents' initiation of conversations as a sign of caring and interest, they seem to be more willing to share information and, by doing so, they seem to try to maintain a close relationship with them. Moreover, in line with previous studies (e.g., Mageau et al, 2017;Wuyts et al, 2018), perceived maternal and paternal autonomy support were positively related to adolescents' disclosure, and negatively associated with secrecy and lies. In other words, when parents are perceived to provide an autonomysupportive parenting context, for example by being sensitive for their children's feelings and by offering choices whenever possible, their adolescents are more likely to disclose information.…”
Section: Discussionsupporting
confidence: 89%
“…In other words, when parents are perceived to provide an autonomysupportive parenting context, for example by being sensitive for their children's feelings and by offering choices whenever possible, their adolescents are more likely to disclose information. As Wuyts et al (2018) suggested, in an autonomy-supportive parenting context, adolescents disclose information because they personally want to (i.e., for volitional reasons), rather than because their parents pressured them to share information (i.e., for controlled reasons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an autonomy-supportive style involves a number of basic practices (i.e., taking the child's perspective, building in desired choice, offering a meaningful rationale for requests, and the use of informational language; Ryan and Deci 2017; Vansteenkiste and Soenens 2015), some of these practices may be more salient, critical and easily applicable in certain contexts and at certain ages than others. To illustrate, parental autonomy support and control manifest differently during a puzzle solving task with toddlers (e.g., Bernier et al 2010) versus during a conversation about sexuality (Mauras et al 2013) or friendships with adolescents (e.g., Wuyts et al 2018).…”
Section: Advancementsmentioning
confidence: 99%
“…Relatedly, autonomy-support fosters open and honest communication in parent-child relationships (Bureau & Mageau, 2014;Wuyts, Vansteenkiste, Soenens, & Van Petegem, 2015). Possibly because of these beneficial effects of parental autonomy support on children's need satisfaction and motivation, autonomy-support is related to adjustment in specific domains of life and to children's and adolescents' overall well-being (Joussemet, Koestner, Lekes, & Landry, 2005).…”
Section: Autonomy-supportmentioning
confidence: 99%